Хангайн мужийн цагираг тогтоцуудын онцлог - Б.Бат (Geological Issues, 2023)
Within Khangaya on the satellite images of different scales, ring structures are perfectly visible. The author limited himself to mentioning only those that have a geomorphological significance. The one of the larger ring structures of the Khangai region is the Upper Orkhongol structure. It is revealed by the arcuate pattern of the axial part of the Suvraga Khairhan ridge and the radial centripetal direction of the tributaries of the upper Orkhongol river drainage system. Ring structures along the Chuluutgol valley are also small structures with a diameter of several kilometers to 70 km. Of particular interest are the ring structures that reveal connections with the Cenozoic basalts of the Khangay. These are all the structures along the valley of Chuluutgol – Upper Orhongol river, Shireet Nuur ring structure, Upper Ongingol river’s ring structure.